A human capital model of the effects of abilities and family background on optimal schooling levels - Tracy L. Regan; Galen Burghardt; Ronald L. Oaxaca (Institute for the Study of Labor (IZA), 2006)
This paper develops a theoretical model of optimal schooling levels where ability and family background are the central explanatory variables. We derive schooling demand and supply functions based on individual wealth maximization. Using NLSY79 data we stratify our sample into one-year FTE work experience cohorts for 1985-1989. Mincer's (1974) overtaking cohort (the years of work experience at which individuals' observed earnings approximately equal what they would have been based on schooling and ability alone) corresponds to 13 FTE years of work experience yielding on average a rate of return of 9.6 percent and an average (optimal) 11.4 years of schooling.
Keywords: J24; J31; J22; 330; human capital; ability; family background; schooling; earnings; Bildungsverhalten; Lohn; Familie; USA